2016
DOI: 10.1007/s00702-016-1544-3
|View full text |Cite
|
Sign up to set email alerts
|

Reduced functional connectivity to the frontal cortex during processing of social cues in autism spectrum disorder

Abstract: People diagnosed with autism spectrum disorder (ASD) characteristically present with severe difficulties in interpreting every-day social signals. Currently it is assumed that these difficulties might have neurobiological correlates in alterations in activation as well as in connectivity in and between regions of the social perception network suggested to govern the processing of social cues. In this study, we conducted functional magnetic resonance imaging (fMRI)-based activation and connectivity analyses foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 48 publications
4
18
0
Order By: Relevance
“…These results are consistent with the notion that the network of the social brain regions is impaired in ASD ( Emery and Perrett, 2000 ; Johnson et al, 2005 ; Frith, 2007 ; Pelphrey and Carter, 2008 ). These results are also consistent with those of several functional neuroimaging studies that have reported reduced functional connectivity in individuals with ASD while engaging in some social tasks, such as facial expression processing ( Welchew et al, 2005 ; Wicker et al, 2008 ; Sato et al, 2012 ), face perception ( Kleinhans et al, 2008 ; Koshino et al, 2008 ; Hoffmann et al, 2016 ; Lynn et al, 2016 ), and mindreading ( Castelli et al, 2002 ). However, structural neuroimaging evidence has been lacking.…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with the notion that the network of the social brain regions is impaired in ASD ( Emery and Perrett, 2000 ; Johnson et al, 2005 ; Frith, 2007 ; Pelphrey and Carter, 2008 ). These results are also consistent with those of several functional neuroimaging studies that have reported reduced functional connectivity in individuals with ASD while engaging in some social tasks, such as facial expression processing ( Welchew et al, 2005 ; Wicker et al, 2008 ; Sato et al, 2012 ), face perception ( Kleinhans et al, 2008 ; Koshino et al, 2008 ; Hoffmann et al, 2016 ; Lynn et al, 2016 ), and mindreading ( Castelli et al, 2002 ). However, structural neuroimaging evidence has been lacking.…”
Section: Discussionsupporting
confidence: 91%
“…It is showed that the dysfunction of ACG in ASD patients is related to the symptoms of behavioral disorders (Thakkar et al, 2008 ). Our results also indicated that the FC of ACG was abnormal, which is related to behavioral disorders in ASD patients (Hoffmann et al, 2016 ). Thirdly, INS is the source of social emotion (Pavuluri and May, 2015 ).…”
Section: Discussionsupporting
confidence: 75%
“…Supporting our results, a recent fMRI study described a reduction of connectivity specifically between the left temporal area and the superior and medial frontal gyrus (Hoffmann et al ., ), regions that have been implicated in higher mental processes strictly related to social functioning, such as mentalizing and reward anticipation (Amodio & Frith, ).…”
Section: Discussionmentioning
confidence: 99%